2023
DOI: 10.1038/s41388-023-02901-5
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid treatment influences prostate cancer cell growth and the tumor microenvironment via altered glucocorticoid receptor signaling in prostate fibroblasts

Andrea Eigentler,
Florian Handle,
Silvia Schanung
et al.

Abstract: Despite significant therapeutic advances in recent years, treatment of metastatic prostate cancer (PCa) remains palliative, owing to the inevitable occurrence of drug resistance. There is increasing evidence that epithelial glucocorticoid receptor (GR) signaling and changes in the tumor-microenvironment (TME) play important roles in this process. Since glucocorticoids (GCs) are used as concomitant medications in the course of PCa treatment, it is essential to investigate the impact of GCs on stromal GR signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Written consent was obtained from all patients and documented in the University Hospital Innsbruck (Austria) database and the medical hospital Carl Gustav Carus Dresden (Germany) in agreement with the statutory provisions. The Innsbruck cohort is represented using a tissue micro-array containing benign and primary cancer tissue cores from 120 treatment-naïve PCa patients who underwent open retropubic or robotic-assisted radical prostatectomy [ 55 ]. This cohort included 92 cancer tissue cores paired with benign tissue cores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Written consent was obtained from all patients and documented in the University Hospital Innsbruck (Austria) database and the medical hospital Carl Gustav Carus Dresden (Germany) in agreement with the statutory provisions. The Innsbruck cohort is represented using a tissue micro-array containing benign and primary cancer tissue cores from 120 treatment-naïve PCa patients who underwent open retropubic or robotic-assisted radical prostatectomy [ 55 ]. This cohort included 92 cancer tissue cores paired with benign tissue cores.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of positively stained cells was scored 0–4 (0 = absent, 1 ≤ 10%, 2 ≤ 50%, 3 ≤ 75%, and 4 ≥ 75%). Both scores were multiplied to obtain an immunoreactivity score (IRS), ranging from 0 to 12 [ 55 , 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…He revealed that GR activation increases stromal GR signalling, altering gene expression, protein levels, cancer-associated fibroblast (CAF) ‘s morphology, and increased protein secretion such as Interleukin (IL-)8 and IPTG [ 42 ]. Consequently, cell growth, colony formation, and 3D-spheroid processes of PCa epithelial cells are affected [ 42 ]. Furthermore, alterations in the adhesion-related proteins of CAFs following GR activation result in extracellular matrix remodelling [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, cell growth, colony formation, and 3D-spheroid processes of PCa epithelial cells are affected [ 42 ]. Furthermore, alterations in the adhesion-related proteins of CAFs following GR activation result in extracellular matrix remodelling [ 42 ]. Therefore, glucocorticoid-mediated GR signalling affects the CAF secretome and extracellular matrix architecture [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation